(untitled) (Scientific journal of the Fergana State University, 2024)
The chemical and mineralogical composition, physico-chemical properties of dolomite from the Jamansai deposit of the Republic of Karakalpakstan have been studied. According to the results of chemical analysis, the content of dolomite in the mineral is almost 99%. According to the results of thermographic analysis, the temperature range of two stages of dolomite dissociation was determined, it was found that the first stage of dolomite dissociation corresponds to a temperature of 713-766 ° C, and the second-780-820 ° C. It has been shown that the dolomite found in Jamansai can be used as a raw material for the production of magnesia bonds.